Hi
Need help to express the following in partial fractions:
$\displaystyle \frac{x^2-2}{(x+1)(x-2)}$
P.S
What do you need to do with this expression?
The order of the numerator is the same as the denominator, you may not need to make partial fractions.
If you need to consider
$\displaystyle \frac{x^2-2}{(x+1)(x-2)} = \frac{A}{x+1}+\frac{B}{x-2}$
$\displaystyle x^2-2 = A(x-2)+B(x+1)$
choose values for x to solve for A and B.
$\displaystyle \frac{x^2-2}{(x+1)(x-2)} = $
$\displaystyle \frac{x^2-2}{x^2-x-2} = $
$\displaystyle \frac{x^2-x-2+x}{x^2-x-2} = $
$\displaystyle \frac{x^2-x-2}{x^2-x-2} + \frac{x}{x^2-x-2} = $
$\displaystyle 1 + \frac{x}{(x+1)(x-2)}$
now use the method of partial fractions on $\displaystyle \frac{x}{(x+1)(x-2)}$